Placental tissue of greenhouse muskmelon (Cucumis melo L.) contains more gamma-aminobutyric acid with antioxidant capacity than the fleshed pulp. Issue 6 (2nd June 2020) - Toyoizumi, Tomoyasu; Ohba, Seiji; Takano-Ishikawa, Yuko; Ikegaya, Atsushi; Nakajima, Teruko
ABSTRACT: Our previous study revealed that gamma-aminobutyric acid (GABA) in Earl's muskmelon is more concentrated in the inner than the outer parts of the fruit. Here, the GABA and antioxidant capacity of the placental tissue of muskmelon, which is considered waste, were evaluated for possible use as a source of bioactive compounds. The concentrations of GABA and related substances in the placental tissue were significantly higher than in the fleshed pulp, whereas glutamic acid and sugar levels were significantly lower. The two sites showed no difference in GAD activity. Furthermore, the placental site showed high antioxidant capacities based on 2, 2-diphenyl-1-picrylhydrazyl and oxygen radical absorbance capacity for hydrophilic compounds assays compared with the fleshed pulp, because of the higher levels of total phenolic and L-ascorbic acids. Therefore, the placental tissue of muskmelons may be useful for developing functional foods, which would also reduce the amount of residues during muskmelon processing. Graphical abstract: : The present study found that the placental tissue in Earl's muskmelon, has a higher GABA concentration and antioxidant capacity than the fleshed pulp.